2017
DOI: 10.1111/jocn.13804
|View full text |Cite
|
Sign up to set email alerts
|

Contributing factors for therapeutic diet adherence in patients receiving haemodialysis treatment: an integrative review

Abstract: Professionals should be trained in health education and communication techniques to contribute to the patient's self-management and motivation for diet adherence. Controlled and randomised clinical studies involving predialysis stages should be performed to investigate the impact of the assessment and control of barriers to diet adherence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
(125 reference statements)
5
20
0
2
Order By: Relevance
“…Family support as a motivator of adherence to integrated management has been highlighted in the study. These results were similar to the findings of Ghimire et al (2017), Griva et al (2013) and González Oquendo et al (2017). Furthermore, family support has been shown to maintain the quality of life and to improve coping mechanisms among patients with CKD (Tannor et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Family support as a motivator of adherence to integrated management has been highlighted in the study. These results were similar to the findings of Ghimire et al (2017), Griva et al (2013) and González Oquendo et al (2017). Furthermore, family support has been shown to maintain the quality of life and to improve coping mechanisms among patients with CKD (Tannor et al, 2017).…”
Section: Discussionsupporting
confidence: 88%
“…In view of few published studies in other regions, social support in the form of family and friends has been included as a motivator of adherence behavior (Ghimire, Castelino, Jose, & Zaidi, 2017;González Oquendo, Morales Asencio, & Bonill de las Nieves, 2017;Maxia et al, 2016). Maxia et al (2016) further highlighted the crucial role of involving family support in the attainment of compliance among patients with CKD.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In fact, depression could be responsible for non-adherence with treatment through behavioural pathways [26]. A recent quantitative review reported that depressed patients with a chronic illness are about threefold noncompliant to medical treatment than non-depressed patients [27]. Similarly, depressive disorder in dialysis was associated with double risk of no compliance to calcium-phosphorus dietary prescriptions [26].…”
Section: Discussionmentioning
confidence: 99%
“…25 Additionally, with depression and self-reported poorer mental health also impacting on activation, 22,23 an interdisciplinary approach to care including psychology may be required to address motivational barriers. 26 In the present study, one in five patients felt they saw a dietitian when they did not need it, and 50% reported a preference to see a dietitian when they have a question or concern rather than at predefined intervals. This suggests that dietetics services for dialysis patients may need to shift towards models with care provided where and when desired by the patient, rather than at set intervals as dictated by guidelines.…”
Section: Percentage Of Respondentsmentioning
confidence: 52%
“…Given these motivational barriers, exploring decisional balance with patients, building relationships and high level motivational interviewing skills of clinicians are likely to be important strategies in supporting people with chronic disease to achieve good health outcomes . Additionally, with depression and self‐reported poorer mental health also impacting on activation, an interdisciplinary approach to care including psychology may be required to address motivational barriers …”
Section: Discussionmentioning
confidence: 99%